Hierarchical plateau and turnover intention of employees at the career establishment stage: Examining mediation and moderation effects. Issue 5 (12th September 2016) - Xie, Baoguo; Xin, Xun; Bai, Guanglin
Abstract : Purpose: Applying the theory of work adjustment (TWA), the purpose of this paper is to investigate whether the effect of hierarchical plateau on the turnover intention of employees at the career establishment stage is mediated by job satisfaction and moderated by person-job fit. Design/methodology/approach: A survey method was used and data were collected from 248 Chinese employees at the career establishment stage. Hierarchical regression analysis and moderated mediation analysis were used to test the hypotheses. Findings: The results demonstrated that hierarchical plateau was positively related to the turnover intention of employees at the career establishment stage and that job satisfaction played a mediating role in the relationship. Person-job fit moderated the relationship between hierarchical plateau and job satisfaction, and the indirect effect of hierarchical plateau on turnover intention via job satisfaction. Originality/value: This research offers new insights into the links between hierarchical plateau and employees' work attitudes and withdrawal behaviour within the TWA. The results suggest that managers can lessen the negative effects of hierarchical plateau on employees' attitudes and withdrawal behaviour by improving employees' overall person-job fit.